African-American Women’s Quest for Happiness in Terry Mcmillan’s Selected Novels - AGUESSY, ANNE NATHALIE JOUVENCIA AGOSSI; MEDEGAN, AMBROISE (My University, 2017)
History has it that the utmost aim of Man’s struggles is the pursuit of happiness. This pursuit of happiness is a legally and constitutionally recognized right of/for all American citizens irrespective of their race, colour, gender and creed. But the concept of happiness is elusive and challenging in nature and its meaning solely depends on an individual’s perception of it. This paper aims to explore Terry McMillan’s perception of this concept in two of her novels: Waiting to Exhale (1992) and Getting to Happy (2010). Given that history holds that African-American women suffered sexism and racism in their society, this study seeks to analyze the selected novels in order to unveil the various mechanisms employed by McMillan to make her female personae cope with gender discrimination and exclusion, both of which are the manifestations of sexism and racism and live a happy life. This study draws on New Historicism for theoretical insight and orientation. With this theory, the paper seeks to take stock of how McMillan’s times affect her works under scrutiny and how these works reflect her times.
Keywords: New Historicism; African-American; contemporary; women; happiness; Terry McMillan’s novels